The global clinical movement : educating lawyers for social justice - Bloch, Frank S. (New York ; Oxford : Oxford University Press, 2011)
Clinical legal education is playing an increasingly important role in educating lawyers worldwide. Here, the contributors describe the central concepts, goals, and methods of clinical legal education from a global perspective, with a particular emphasis on its social justice mission.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed Dec. 16, 2010).
Keywords: Law -- Study and teaching (Clinical education)